1988
DOI: 10.1111/j.1365-2818.1988.tb01444.x
|View full text |Cite
|
Sign up to set email alerts
|

A real space investigation of the dimer defect structure of Si(001)‐(2times8)

Abstract: KEY WORDS. Real space imaging, Si(001)-(2x8). SUMMARY The atomic arrangement of the Si(001)-(2 x 8) surface has been directly imaged in real space by scanning tunnelling microscopy. The superstructure is impurity induced and stablilized by as little as 1% Ni. Clean Si(OO1) surfaces do not form the (2x8) phase. The two-dimensional Fourier transforms of the STM topographs correspond well to the (2x8) LEED pattern, but the real space images are in fact considerably more complex than previously concluded on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(43 citation statements)
references
References 13 publications
5
38
0
Order By: Relevance
“…A classic example is the case of Ni on Si͑001͒, in which concentrations of as little as 5% create arrays of line vacancies. 22,23 We observe an unusual structure on this surface that does not appear to have been noted in the past. Two examples are highlighted with arrows in Fig.…”
Section: Report Documentation Pagementioning
confidence: 67%
“…A classic example is the case of Ni on Si͑001͒, in which concentrations of as little as 5% create arrays of line vacancies. 22,23 We observe an unusual structure on this surface that does not appear to have been noted in the past. Two examples are highlighted with arrows in Fig.…”
Section: Report Documentation Pagementioning
confidence: 67%
“…4. It has been reported by several researchers that Ni impurities induce the 2×n structure [44,46,48,52]. It is noted that such Ni contamination also occurs on the Si(111) surface, leading to the √ 19 × √ 19 structure [89,101].…”
Section: B 2 × N Reconstructionmentioning
confidence: 99%
“…In the first stage carbonization of a Si(100) surface, 2 × n (6 ≤ n ≤ 12) [27,28] and c(4 × 4) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] reconstructions have been reported. However, similar 2 × n [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and c(4 × 4) reconstructions have been reported without carbonization. It is noteworthy that X-ray photoelectron diffraction (XPD) studies [5,26,[36][37][38][39][40] have indicated an absence of carbon atoms on the outermost layer of the c(4 × 4) surface induced by carbon.…”
Section: Introductionmentioning
confidence: 99%
“…), or metal contamination [14][15][16][17][18] (Ni, Cu, Co, Ag, etc.). For sufficiently high temperatures those missing dimers order into vacancy islands.…”
mentioning
confidence: 99%